2018
DOI: 10.1111/nhs.12586
|View full text |Cite
|
Sign up to set email alerts
|

Nurses' organizational communication satisfaction, emotional labor, and prosocial service behavior: A cross‐sectional study

Abstract: In this study, we investigated nurses' organizational communication satisfaction and emotional labor in an attempt to identify the factors that influence nurses' prosocial service behavior in Korea. A cross‐sectional study was conducted on 145 nurses at two Korean tertiary hospitals in 2017. Most participants (89%) were female, and the mean age was 28.45 ± 5.50 years; data analysis was mainly based on a multiple regression. It was consequently found that nurses' organizational communication satisfaction and em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 38 publications
1
11
0
1
Order By: Relevance
“…The scores on communication satisfaction were consistent with previous studies with nurses working in operating theaters 22 and university hospitals 17,28 in Korea and public hospitals in South Africa, 29 but lower than those reported by intensive care unit nurses in Belgium. 30 The highest-scored subdomains were supervisor communication and horizontal communication, which is consistent with previous reports, 17,28 whereas organizational integration, personal feedback, and organizational perspective scored lower. These results indicated that nurses are the most satisfied with interpersonal communication but less satisfied with organizational aspects.…”
Section: Communication Satisfactionsupporting
confidence: 89%
See 1 more Smart Citation
“…The scores on communication satisfaction were consistent with previous studies with nurses working in operating theaters 22 and university hospitals 17,28 in Korea and public hospitals in South Africa, 29 but lower than those reported by intensive care unit nurses in Belgium. 30 The highest-scored subdomains were supervisor communication and horizontal communication, which is consistent with previous reports, 17,28 whereas organizational integration, personal feedback, and organizational perspective scored lower. These results indicated that nurses are the most satisfied with interpersonal communication but less satisfied with organizational aspects.…”
Section: Communication Satisfactionsupporting
confidence: 89%
“…Previous studies also reported that nurses were the least satisfied with information they received on organizational perspectives. 28,30 Moreover, the Korean tradition of elder respect rooted in the Confucian and the Korean health care hierarchical organizational culture would enhance the level of satisfaction with supervisor communication. Nevertheless, organizational-level communication was the lowest at 2.72, showing that an improvement is necessary, including organizational policies and long-term plans, through open communication and information sharing between the executive level and individual nurses.…”
Section: Communication Satisfactionmentioning
confidence: 99%
“…When the organizational climate in an organization is built positively or well developed, it increases positive behavior or attitudes, job satisfaction, and communication satisfaction among members. 23 , 24 An open communication climate is needed in hospital services because it is multidisciplinary and has the potential for conflict due to efficiency. In health care, 70-80% of the errors that occur are caused by poor communication and understanding within the team.…”
Section: Resultsmentioning
confidence: 99%
“…Nurses' experiences of constantly regulating their emotions have been researched mostly in Western hospital contexts (Bartram et al, 2012;Delgado et al, 2020;Delgado et al, 2017;Theodosius et al, 2021). A number of studies have explored nurses' experiences of managing their emotions in Asian contexts such as Korea (Han et al, 2018;Kim & Jang, 2018), India (Roopalekha et al, 2012;Thomas & Abhyankar, 2014), Iran (Zamanzadeh et al, 2013), China (Liu et al, 2020;Zhou et al, 2015) and Pakistan (Banning & Gumley, 2012). Emotional labour in Sri Lanka is heavily under-researched where a few studies have explored emotional labour among school teachers (Dias & Bhadra, 2014), bank tellers (Kodikara & De Alwis, 2015;Perera & Arachchige, 2014), academics in state universities (Thisera & Bandara, 2018), and cabin crew and frontline airport staff (Perera & Kailasapathy, 2013).…”
Section: Emotional Labour Gender and Nursingmentioning
confidence: 99%